Safety design for space systems - Musgrave, Gary Eugene, 1947-; Larsen, Axel M.; Sgobba, Tommaso (Elsevier/Butterworth Heinemann, 2009)
Progress in space safety lays in the acceptance of safety design and engineering as an integral part of the design and implementation process for new space systems. Safety must be seen as the principle design driver of utmost importance from the outset of the design process, which is only achieved through a culture change that moves all stakeholders toward front-end loaded safety concepts. This approach entails a common understanding and mastering of basic principles of safety design for space systems at all levels of the program organization. Fully supported by the International Association for the Advancement of Space Safety (IAASS), written by the leading figures in the industry with frontline experience from projects ranging from the Apollo missions, Skylab, the Space Shuttle and the International Space Station, this book provides a comprehensive reference for aerospace engineers in industry. Provided by publisher.
Sponsored by the International Association for the Advancement of Space Safety.
Keywords: Astronautics -- Safety measures.; elektronické knihy; electronic books